ENVIRONMENTAL COST AND AUDIT COMMITTEE ON FINANCIAL PERFORMANCE - Seveny Amelia Lingga; Harman Malau; Mila Susanti (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2026)
This study aims to examine the effect of environmental cost and the audit committee on the financial performance of companies listed on the Main Board of the Indonesia Stock Exchange in 2024. Despite increasing attention to environmental governance and corporate oversight, prior studies have predominantly analyzed these variables separately, leaving a gap in understanding their simultaneous impact, particularly in the context of large-capitalization firms in emerging markets such as Indonesia. This research employs a quantitative approach with purposive sampling, resulting in 164 firm-year observations. Data were obtained from companies’ annual and sustainability reports for 2024. Financial performance is proxied by Return on Assets (ROA), and the hypotheses are tested using multiple linear regression with SPSS version 26. The results indicate that environmental cost and the audit committee, both partially and simultaneously, do not have a significant effect on financial performance. The coefficient of determination (R²) is close to zero, indicating very limited explanatory power of the model in explaining variations in ROA. These findings suggest that environmental expenditures among large firms remain predominantly compliance-oriented rather than strategically value-enhancing, while the audit committee tends to function more as a formal governance mechanism rather than an effective driver of financial performance. Theoretically, this study contributes to stakeholder theory and agency theory by highlighting the limited short-term and lagged financial impact of environmental and governance mechanisms. Practically, the findings provide insights for companies and regulators to strengthen the strategic role of environmental cost allocation and improve the effectiveness of audit committees in supporting long-term value creation.